PERANAN LITERASI KEUANGAN DAN FINANCIAL SELF-EFFICACY TERHADAP POLA PERILAKU KONSUMTIF MAHASISWA SEKOLAH TINGGI ILMU EKONOMI NUSANTARA MAKASSAR - Muhammad Yani; Zulkifli Zulkifli (Universitas Ichsan Sidenreng Rappang, 2025)
This research aims to analyze the role of financial literacy and financial self-efficacy on the consumer behavior patterns of students. Consumerism is a critical issue in the era of globalization, where consumptive behavior, characterized by excessive purchasing without a clear function, is growing. Theoretically, financial literacy equips individuals with the knowledge and skills for financial management, while financial self-efficacy is the self-belief in one's ability to manage finances effectively. The research employed a quantitative method with a descriptive-survey approach. The study population was 481 students in the odd semester of 2024, with a sample of 83 respondents determined using the Slovin formula. Data were collected through questionnaires, observation, and interviews, and then analyzed using multiple linear regression after validity, reliability, and classical assumption tests. The hypothesis test results (F-test and t-test) show that financial literacy and financial self-efficacy, both simultaneously and partially, do not have a significant effect on students' consumptive behavior. The coefficient of determination (R2) of 0.050 indicates that the two independent variables only explain 5% of the variation in consumptive behavior, with the remaining 95% being influenced by other factors outside the research model. These findings suggest that students' financial knowledge and self-confidence may be inadequate or not yet internalized in daily practice, and their consumptive behavior is more influenced by external variables such as lifestyle or social environment pressure. Therefore, students are advised to be wiser in using money and avoid unnecessary consumptive behavior.